Radiation-and-temperature resources of the steppe zone in Ukraine under the climate change conditions in the period of up to 2050 - А. N. Polevoy; O. V. Shabliy (Український гідрометеорологічний журнал, 2016)
Indices of the radiation-and-temperature regime in the Steppe zone of Ukraine in the period of 1986 through 2005, as compared to the expected changes in these indices, calculated in accordance with the two climate change scenarios, RCP4.5 and RCP8.5, for the period of up to 2050, are under consideration in the paper. RCP4.5 is a scenario of stabilization of greenhouse gas emissions into the atmosphere, while RCP8.5 is the one of very high greenhouse gas emissions. To characterize the radiation and thermal resources in the Steppe zone of Ukraine in the period of 1986 through 2005 (the basic period), and the change in the period of 2021 through 2050 calculations of average long-term values for the first group of environmental factors were performed: the duration of daytime, the total daily solar radiation, the intensity of photosynthetically active radiation (PAR), the accumulated PAR, the radiation balance of the vegetation cover, and the temperature regime. The following principal agro-climatic characteristics of the temperature regime were considered: dates of stable rise of the air temperature above 0, 5, 10, 15 °C in spring and autumn, duration of the period with air temperatures above 0, 5, 10, 15 °C, the accumulated positive air temperatures for the period with air temperatures above 0, 5, 10, 15 °C, the average air temperature in January and July, and the amplitude.